2018
DOI: 10.4236/ojpm.2018.810026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lemon Beverages on Bone Metabolism and Bone Mineral Density in Postmenopausal Women: A Double-Blind, Controlled Intervention Study with Ca-Supplemented and Unsupplemented Lemon Beverages

Abstract: The aim of the present study was to elucidate how bone metabolism and bone mineral density are affected by the consumption of a lemon juice-containing calcium (Ca)-enriched beverage. The efficacy of this investigational product was evaluated in postmenopausal women during five months of continuous intake (intervention). This was a randomized, controlled trial. Eighty-three subjects were assigned to three groups. Using a double-blind format, the first two groups received a Ca-supplemented lemon-juice (lemon) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…e sample size was determined according to the 6-month difference regarding bone mineral density in the lumbar spine using G-power. Based on the results of a prior study conducted by Ikeda et al [9] on the relationship between an LECA group and control group and after considering M1 � 0.021 (mean BMD of 6 months, difference in the control group), SD 1 � 0.020, M2 � -0.027 (mean BMD of 6 months difference in the LECA group), SD2 � 0.041, two-sided α � 0.05, and power � 95%, the minimum number of subjects per group was determined to be 15, which was increased to 23 (minimum sample size of the control group) to take account for potential attrition, making the total sample size 79. us, 79 individuals who participated in all medical examinations conducted at the start of the trial prior to consuming a test beverage, as well as 5 and 11 months after starting consumption ingestion, were subjected to analysis. e subjects included those who had not been diagnosed with osteoporosis but were at a level indicating such a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e sample size was determined according to the 6-month difference regarding bone mineral density in the lumbar spine using G-power. Based on the results of a prior study conducted by Ikeda et al [9] on the relationship between an LECA group and control group and after considering M1 � 0.021 (mean BMD of 6 months, difference in the control group), SD 1 � 0.020, M2 � -0.027 (mean BMD of 6 months difference in the LECA group), SD2 � 0.041, two-sided α � 0.05, and power � 95%, the minimum number of subjects per group was determined to be 15, which was increased to 23 (minimum sample size of the control group) to take account for potential attrition, making the total sample size 79. us, 79 individuals who participated in all medical examinations conducted at the start of the trial prior to consuming a test beverage, as well as 5 and 11 months after starting consumption ingestion, were subjected to analysis. e subjects included those who had not been diagnosed with osteoporosis but were at a level indicating such a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Informed written consent was obtained from 100 volunteers. e present study was conducted as a randomized control trial using methods previously reported by Hua et al in 2018 [7,9]. e subjects were given individual ID numbers to assure anonymity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our group examined the effectiveness of a Ca-supplemented lemon beverage for the prevention of osteoporosis in postmenopausal women who had regularly consumed the beverage for five months [18].…”
Section: Trial Registrationmentioning
confidence: 99%
“…Despite these limitations, unprecedented results were obtained from this clinical research, which was conducted with subjects who consumed a Ca-supplemented investigational product, while otherwise leading their normal lives. In our previous study [18], in which the effects of the same investigational products were assessed after five months of intervention, we proposed a hypothesis that citric acid in lemons increases the absorption of 4 bone alkaline phosphatase 5 standard deviation 6 They received an unsupplemented lemon beverage. 7 They received a lemon beverage supplemented with Ca.…”
Section: Changes In the Concentrations Of Bone Metabolism Markersmentioning
confidence: 99%